Shear and bond behaviour of reinforced fly ash-based geopolymer concrete beams - Chang, Ee Hui (Curtin University, 2009)
Concrete is by far the most widely used construction material worldwide in terms of volume, and so has a huge impact on the environment, with consequences for sustainable development. Portland cement is one of the most energy-intensive materials of construction, and is responsible for some emissions of carbon dioxide — the main greenhouse gas causing global warming. Efforts are being made in the construction industry to address these by utilising supplementary materials and developing alternative binders in concrete; the application of geopolymer technology is one such alternative. Indeed, geopolymers have emerged as novel engineering materials with considerable promise as binders in the manufacture of concrete. Apart from their known technical attributes, such as superior chemical and mechanical properties, geopolymers also have a smaller greenhouse footprint than Portland cement binders.Research on the development, manufacture, behaviour and applications of low calcium fly ash-based geopolymer concrete has been carried out at Curtin University of Technology since 2001. Past studies of the structural behaviour of reinforced fly ash-based geopolymer concrete members have covered the flexural behaviour of members. Further studies are needed to investigate other aspects of the structural behaviour of geopolymer concrete. Design for both shear and bond are important in reinforced concrete structures. Adequate shear resistance in reinforced concrete members is essential to prevent shear failures which are brittle in nature. The performance of reinforced concrete structures depends on sufficient bond between concrete and reinforcing steel. The present research therefore focuses on the shear and bond behaviour of reinforced low calcium fly ash-based geopolymer concrete beams.For the study of shear behaviour of geopolymer concrete beams, a total of nine beam specimens were cast. The beams were 200 mm x 300 mm in cross section with an effective length of 1680 mm. The longitudinal tensile reinforcement ratios were 1.74%, 2.32% and 3.14%. The behaviour of reinforced geopolymer concrete beams failing in shear, including the failure modes and crack patterns, were found to be similar to those observed in reinforced Portland cement concrete beams. Good correlation of test-to-prediction value was obtained using VecTor2 Program incorporating the Disturbed Stress Field Model proposed by Vecchio (2000). An average test-to-prediction ratio of 1.08 and a coefficient of variation of 8.3% were obtained using this model. It was also found that the methods of calculations, including code provisions, used in the case of reinforced Portland cement concrete beams are applicable for predicting the shear strength of reinforced geopolymer concrete beams.For the study of bond behaviour of geopolymer concrete beams, the experimental program included manufacturing and testing twelve tensile lap-spliced beam specimens. No transverse reinforcement was provided in the splice region. The beams were 200 mm wide, 300 mm deep and 2500 mm long. The effect of concrete cover, bar diameter, splice length and concrete compressive strength on bond strength were studied. The failure mode and crack patterns observed for reinforced geopolymer concrete beams were similar to those reported in the literature for reinforced Portland cement beams. The bond strength of geopolymer concrete was observed to be closely related to the tensile strength of geopolymer concrete. Good correlation of test bond strength with predictions from the analytical model proposed by Canbay and Frosch (2005) were obtained when using the actual tensile strength of geopolymer concrete. The average ratio of test bond strength to predicted bond strength was 1.0 with a coefficient of variation of 15.21%. It was found that the design provision and analytical models used for predicting bond strength of lapsplices in reinforced Portland cement concrete are applicable to reinforced geopolymer concrete beams.